Kaolinite induces rapid authigenic mineralisation in unburied shrimps - Nora Corthésy; Farid Saleh; Jonathan B. Antcliffe; Allison C. Daley (Communications Earth & Environment)
Abstract Fossils preserving soft tissues and lightly biomineralized structures are essential for the reconstruction of past ecosystems and their evolution. Understanding fossilization processes, including decay and mineralisation, is crucial for accurately interpreting ancient morphologies. Here we investigate the decay of marine and freshwater shrimps deposited on the surface of three different clay beds. In experimental set ups containing kaolinite, cryogenic scanning electron microscopy shows a black film comprised of newly formed anhedral and cryptocrystalline aluminosilicates on marine shrimp cuticles, which stabilise the overall morphology. This is the first experimental evidence for the replication of arthropod lightly biomineralized structures in aluminosilicates shortly after death, while carcasses are not buried by sediments. The preservation of morphology through aluminosilicates could result in carcasses persisting on the seafloor for weeks without losing much external anatomical information. In this context, instantaneous burial capturing animals alive may not be a prerequisite for exceptional preservation as usually thought.